The Tradition of Tarekat Qadiriyah wa Naqsabandiyah in Pekanbaru, Riau - Masduki, Masduki; Hartono, Toni; Rosidi, Imron (KALAM, 2018)
This article describes the tradition practiced by the followers of Qadiriyah wa Naqsabandiyah in Pekanbaru, Riau. By employing a qualitative approach, this article finds that that the tradition of the Tarekat Qadiriyah wa Naqsabandiyah in Pekanbaru, Riau emerged from the tradition (custom) performed at Pondok Pesantren Nurul Huda al-Islami. Through the pesantren, the tarekat tradition is spread gradually in the practice of education and socialization. From the tradition of pesantren education, this tarekat philosophy is then socialized to the surrounding community's environmental traditions. Philosophically, this study also concluded that tarekat is a doctrine that is close to Islamic education. Pesantren as the center of tarekat development becomes 'icon' development of Islamic education based on Sufi character. In the contemporary context, the values of Sufi education are increasingly crucial, especially in responding to the patterns and lifestyles of consumptive ones arising from modernization, capitalism, and globalization